PENGARUH KOHESIVITAS, GAYA KEPEMIMPINAN DAN MOTIVASI TERHADAP KEAKTIFAN ANGGOTA KELOMPOK TANI GONDANG LESTARI - Sekar Ayu Anjany; Kadhung Prayoga; Agus Subhan Prasetyo (Universitas Galuh, 2022)
Cohesiveness, leadership style of the farmer group leader and motivation are important in determining the activity of members to achieve the goals of the farmer group itself. This study aims to analyze the effect of cohesiveness, leadership style and motivation on the activeness of members of the Gondang Lestari Farmer Group. This research was conducted in January – February 2022, located in the Gondang Lestari Farmer Group, Alastuwo Village, Poncol District, Magetan Regency. The sampling method used was census with the number of respondents as many as 50 members of farmer groups. Methods of data collection was done by interview, observation and documentation. The data analysis method used was descriptive quantitative method in the form of multiple linear regression analysis. The results of the study indicate that the independent variables have a significant effect on the dependent variable together. This means that cohesiveness, leadership style and motivation have an effect on the activeness of members of the Gondang Lestari Farmer Group. Partially, the cohesiveness variable did not affect the activeness of members of the Gondang Lestari Farmer Group, while leadership style and motivation affect the activeness of members of the Gondang Lestari Farmer Group. Suggestions for the future, for farmer group administrators it is necessary to look for more interesting ideas to increase the participation of group members, for example establishing partnerships with companies and for farmer group members, it is necessary to increase activity in developing farmer groups by diligently attending and giving opinions in meetings routinely, paying dues and participating in counseling held as village programs in order to achieve common goals and later be able to support progress in their respective farms.